MODEL OF ADMINISTRATIVE-TERRITORIAL ORGANISATION USING THE CONCEPT OF GEOGRAPHICAL AXIS. CASE STUDY: SOMEȘUL MARE HYDROGRAPHICAL AXIS - Alexandru Marius TĂTAR (Revista Română de Geografie Politică)
The social-economic need for reorganisation of Romania's territory serves as the main purpose in building a model of administrative-territorial organization based on a geographical axis, which can be very useful in understanding and managing regional resources and development more effectively. In the case of the Someșul Mare hydrographical axis, how the localities along this axis develop and interact is investigated. At the level of Bistriţa-Năsăud county, the design of the UAT (administrative-territorial unit) Someșul Mare, which includes the following UATs, is analyzed Șanț, Rodna, Maieru, Anieș, Sângeorz-Băi, Iva Mică, Feldru, Nepos, Poderei, Rebrișoara, Năsăud, Salva, Nimigea, Chiuza, Beclean. The merger of 12 UATs into a single UAT called Someșul Mare with the centre at Beclean. Due to its economic expansion and geographical position, the city has been chosen as the centre and pole of the new U.A.T within the county. National Road 17 (DN 17) and County Route 172 ensure the continuity and functionality of the UAT axis Someșul Mare.